Perl 6 Essentials - Randal, Allison (O'Reilly, 2011)
Perl 6 Essentials is the first book that offers a peek into the next major version of the Perl language. Written by members of the Perl 6 core development team, the book covers the development not only of Perl 6 syntax but also Parrot, the language-independent interpreter developed as part of the Perl 6 design strategy. This book is essential reading for anyone interested in the future of Perl. It will satisfy their curiosity and show how changes in the language will make it more powerful and easier to use.